Study of clinical profile of patients of bipolar mood disorder with and without substance abuse and clinical course variables in the substance abusing bipolar group in one of the tertiary care centre of North India - Sharma, Vineet; Garg, Sunny; Sharma, Dinesh D.; Chauhan, Alka; Sharma, Milli (International Journal of Research in Medical Sciences, 2020)
Background: Bipolar disorder is the sixth leading cause of disability worldwide and has a lifetime prevalence of about 3% in general population. In patients with bipolar disorder there was 58 % lifetime prevalence of co-occurring alcohol abuse and a 38 % lifetime prevalence of co-occurring other substance abuse. Substance abuse interferes with treatment and management approaches of the bipolar disorder. Methods: A cross sectional observational study of 120 male patients divided in substance abusing (60) and non-substance abusing groups (60) with bipolar disorder according to DSM-V, who met the Inclusion criteria . A written informed consent was obtained from the patients and/ or their family members. Patient’s information was recorded on the socio-demographic and clinical profile sheet .Thereafter, YMRS or HAM-D scales were applied as per the phase of the illness. Results: Most of the patients were between 15-25 years in SAB group and 35-50 years in NSAB group, educated, semiskilled and married. Tobacco abuse was the commonest followed by cannabis and alcohol abuse. The mean duration of hospital stay in SAB group was 41.40 days and in NSAB group was 43.20 days. Dysphoric mania, aggressive behavior and suicidal attempts were more in SAB group. Mean total YMRS score of SAB group was greater than NSAB group. Conclusions: Maximum patients had onset of substance abuse before the onset of affective symptoms. Manic symptomatology was more severe in substance abusing group.